1999
DOI: 10.1002/jlb.66.6.974
|View full text |Cite
|
Sign up to set email alerts
|

Role of IFN-γ on dissociation between nitric oxide and TNF/IL-6 production by murine peritoneal cells after restimulation with bacterial lipopolysaccharide

Abstract: Murine peritoneal exudate cells (PEC) pre-exposed to bacterial lipopolysaccharide (LPS) show augmented

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…These findings have been confirmed in mouse thioglycollate-elicited peritoneal macrophage and murine peritoneal exudate cells. 124,125 However, some studies have demonstrated decrease NO production in LPS-tolerant cells. 126 These studies may reflect differences in the tolerance-inducing regimen.…”
Section: Autocrine Mediators Of Endotoxin Tolerancementioning
confidence: 99%
“…These findings have been confirmed in mouse thioglycollate-elicited peritoneal macrophage and murine peritoneal exudate cells. 124,125 However, some studies have demonstrated decrease NO production in LPS-tolerant cells. 126 These studies may reflect differences in the tolerance-inducing regimen.…”
Section: Autocrine Mediators Of Endotoxin Tolerancementioning
confidence: 99%
“…This mechanism is, however, hard to consider as the main underlying mechanism of LPS‐induced IFN‐γ production in vivo , in view of the large amount of IFN‐γ (detectable as protein level) secreted in the serum of mice after LPS challenge. Recently, LPS‐induced production of IFN‐γ in large amounts in in vitro systems was reported by our group using murine peritoneal cells [23] and by other groups using murine spleen cells [24,25]. These results indicate that additional cellular populations, besides the macrophage population, are required for effective production of IFN‐γ in response to LPS, unlike the production of the usual LPS mediators such as IL‐1, IL‐6 and tumor necrosis factor‐α (TNF‐α), for which the macrophage population alone is sufficient.…”
mentioning
confidence: 99%
“…In the course of our study concerning the mechanism of LPS‐induced NO production, participation of IFN‐γ was not suggested when murine macrophage cell lines such as RAW264.7 [26] and J774.1 [27] were used. However, in a study using murine peritoneal cells [23], participation of endogenously produced IFN‐γ in LPS‐induced NO production was thought to occur. In the present study, we aimed to clarify the role of IFN‐γ in LPS‐induced NO production and revealed the important role of IFN‐γ as a key mediator in the main pathway for LPS‐induced NO production in murine peritoneal cell culture.…”
mentioning
confidence: 99%
“…The culture medium was removed gently by aspiration and changed to fresh culture medium. The PECs used for experiments routinely contained 87% to 92% macrophages (34). Then, cell lines were implanted into these wells at a ratio of 1:1.…”
Section: Methodsmentioning
confidence: 99%